Health and the prison system from the perspective of prison primary care professionals: An integrative review (Research, Society and Development, 2024)
The objective of this work is to analyze health care in Brazilian penitentiaries, based on reports from prison basic care teams. This is an integrative literature review carried out through the Google Scholar, SciELO and Portal de Periódicos da CAPES, where, based on the PRISMA 2020 protocol, works published between 2019 and 2023 in Portuguese were selected, excluding duplicated works that did not specifically address the topic or did not present empirical and original data. 492 works were identified, leaving 11 original articles that made up the final sample, which illustrated the health conditions and determinants of different penitentiaries in 8 Brazilian states, where it was observed, based on empirical reports, that the performance of health teams in the prison system it is undermined by problems arising from structural, hygiene, sanitation, food and security conditions. Due to the multifaceted context represented by Brazilian prison establishments, a set of problems are observed that hinder the development of prevention and health promotion actions in these areas, contradicting the provisions of the Brazilian legal system, as well as international conventions and treaties that deal with primary health care.